Analysis of Some Groups and Subgroups of Diplomatic Terminology In English - Xonto`rayeva Yulduz Kenjaboy qizi; Xolibekova Omongul Kenjaboyevna (Zien Journals, 2023)
Diplomacy serves as a crucial tool for building connections and preserving peace with other countries. While it may appear straightforward, preparing specialists in this field involves much more than simply nurturing negotiation skills. This process necessitates a thorough understanding of the basic rules of international communication protocol and etiquette. Additionally, mastering the terminology system within the realm of diplomacy requires comprehensive analysis and study to operate effectively in this sphere. This article aims to dissect diplomatic terminology, focusing on constituent terminological groups and subgroups in diplomacy
Keywords: terminology; diplomacy; formal discourse